SAT0259 ANCA-ASSOCIATED VASCULITIS WITH RENAL INVOLVEMENT: THE ROLE OF A COMBINED HISTOPATHOLOGICAL ASSESSMENT AS PREDICTOR OF PATIENTS' PROGNOSIS. (2nd June 2020) - Gigante, L.; Cerasuolo, P. G.; Vischini, G.; Federico, F.; Bruno, D.; Musto, A.; Costanzi, S.; Bosello, S. L.; Gremese, E.
Abstract : Background: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis often affect the kidney and renal involvement has a considerable clinical impact on patient's prognosis. Currently used histopathological classifications are basically focused on the glomerular damage and assessing chronic damage progression, but their prognostic role presented some limitations. Objectives: To combine the Berden Classification, the ANCA Renal Risk Score (ARRS) and the Mayo Clinic-Renal Chronicity Score (RCS) with the inflammatory interstitial infiltrate and to evaluate the prognostic value of the combined assessment in patients with AAV Methods: We included 19 AAV patients with renal involvement (mean age 63±13.2 years; disease duration 4.9±5.2 months) who underwent renal biopsy. Patients were classified according to age, sex, disease duration, ANCA positivity. The histopathological evaluation was performed assessing the Berden category, Risk group (low, medium, high) according to the ARRS and Chronicity class according to the RCS; we also assessed the % of inflammatory interstitial infiltrate. Each patient was followed-up for 12 months; we considered the stage IV (eGFR < 30 ml/min/m 2 ) of the KDIGO CKD Classification as renal outcome. Results: 8 (42.1%) AAV patients were p-ANCA and 11 (57.9%) c-ANCA. 12 months after renal biopsy, 8 patients (42.1%) had a GFR <30 ml/min. According to the ARRS, 10 (52.6%) patients were in low, 7 (36.8%) in medium and 2 (10.5%) in high risk group. According to the RCS, 2 (10.5%) biopsies had minimal, 10 (52.6%) mild and 7 (36.8%) moderate chronic changes, no one presented severe chronic changes. According to the Berden classification, 6 (31.6%) samples represented the focal, 2 (10.5%) the crescentic and 11 (57.9%) the mixed category, no one represented the sclerotic class. The mean % of inflammatory infiltrate was 37.4±25.2. The interstitial inflammatory infiltrate showed a direct correlation with the severity of the Berden category (R=0.51; p=0.025), the % of sclerotic glomeruli (R=0.6; p=0.007) and the number of fibrocellular crescents (0.46; p=0.05) and an inverse correlation with the GFR at 12 months (R=-0.48; p=0.045). A ROC curve study identified a 22.5% cut-off of inflammatory infiltrate to predict the outcome of GFR at 12 months < 30 ml/min (sensitivity 88%, specificity 97.5%). Patients in focal class developed less frequently a GFR<30 (χ2=9.1; p=0.003), but there were no differences in the outcomes between the crescentic and mixed class. ARRS could differentiate risk group with regard to the renal outcome stage IV (χ 2 =9.0 e p=0.01) as well as the chronicity Score (χ 2 =8.1; p=0.017). Finally, we built a matrix combining the different histopathological scores and the % of inflammatory infiltrate to predict the outcome; we found that an inflammatory infiltrate wider than 22.5% characterizes most of patients developing stage IV chronic renal failure at the 12th month. In fact, more than 75% of patients with eGFR < 30 ml/min had inflammatory infiltrate wider than 22.5% at biopsy, despite they were in the low risk class (ARRS) and in minimal changes class (RCS). Conclusion: Our results underline the importance of the inflammatory infiltrate in renal outcome and histology. Despite the limited number of patients, our data suggest that a combined histological score assessing the chronicity and activity of renal disease from both glomerular and interstitial perspective could better predict patients' global and renal prognosis. References: [1]Berden, J Am Soc Nephrol, 2010 Berti, Nephrol Dial Transplant 2018 Brix, Kidney Int. 2018 Disclosure of Interests: Laura Gigante: None declared, Pier Giacomo Cerasuolo: None declared, Gisella Vischini: None declared, Francesco Federico: None declared, Dario Bruno: None declared, Alessia Musto: None declared, Stefano Costanzi: None declared, Silvia Laura Bosello Speakers bureau: Abbvie, Pfizer, Boehringer, Elisa Gremese Speakers bureau: Abbvie, BMS, Celgene, Jannsen, Lilly, MSD, Novartis, Pfizer, Sandoz, UCB